Microparticles and blood cells induce procoagulant activity via phosphatidylserine exposure in NSTEMI patients following stent implantation. (15th November 2016) - Wang, Lixiu; Bi, Yayan; Cao, Muhua; Ma, Ruishuang; Wu, Xiaoming; Zhang, Yan; Ding, Wenbo; Liu, Yan; Yu, Qian; Zhang, Yingqian; Jiang, Hua; Sun, Yingchun; et al.
Abstract: Background: Relatively little is known about the role of phosphatidylserine (PS) in procoagulant activity (PCA) in patients with non-ST-elevated myocardial infarction (NSTEMI) after stent implantation. This study was designed to evaluate whether exposed PS on microparticles (MPs) and blood cells were involved in the hypercoagulable state in NSTEMI patients with stent implantation. Methods: NSTEMI patients (n= 90) and healthy controls (n = 20) were included in our study. PS exposure on MPs and blood cells was analyzed with flow cytometer and confocal microscope. PCA was evaluated by clotting time, purified coagulation complex assays and fibrin production assays. Results: Baseline levels of MPs and PS + blood cells were significantly higher (P < 0.001) in the patients than in controls. After stent implantation, a remarkable increase was observed in both MPs and PS + blood cells. Specifically, PS + MPs, PS + platelets and erythrocytes peaked at 18 h following stent implantation, while PS + leukocytes peaked on day 2. In addition, circulating MPs (mostly derived from platelets, leukocytes, erythrocytes and endothelial cells) cooperating with PS + blood cells, contributed to markedly shortened coagulation time and markedly increased FXa/thrombin/fibrin (all P < 0.01) generation in patient group. Moreover, blockade of exposed PS on MPs and cells with lactadherin inhibited PCA by approximately 70%. Conclusions: Our results suggest that PS + MPs and blood cells play a procoagulant role in NSTEMI patients following stent implantation. Blockade of PS could become a novel therapeutic modality for the prevention of thrombosis in these patients.